Jatropha curcas L.: Aspek Botani, Potensi Biofuel, Toksisitas, dan Bioaktivitas - Marina Silalahi (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study aims to explain the use (biofuel) and toxicity of J. curcas. This study is based on an online literature study on Google Scholar using the keywords J. Curcas and toxicity of J. curcas. Inedible vegetable oil (biodiesel), such as castor oil, is considered a future raw material because it is a non-edible oil and does not cause food versus fuel conflicts. The potential of J. curcas as a biofuel is related to the oil content consisting of saturated fatty acids, palmitic acid, stearic acid and unsaturated fatty acids, oleic acid, and linoleic acid. Poisoning due to side effects of J. curcas seeds occurs in humans, especially children and also in the environment. Symptoms of poisoning caused by J. curcas can be analyzed through clinical signs, and the effects vary greatly, depending on the concentration, frequency, part eaten and the processing process. Accidentally ingested J. curcas seeds cause clinical syndromes such as restlessness, severe vomiting, and dehydration. Curcacycline A and curcin compound have been successfully identified from J. curcas with antitumor activity. The potential of J. curcas as an antitumor needs to be studied further to find alternative treatments for cancer and tumours.